Some New Results in the $q-$Calculus - Medina, Jorge A. Castillo; 'ia, Salvador Cruz Garc; Valdes, Juan E. N 'apoles; Moyaho, Thelma Galeana (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we present some results for a fractional derivative of type $q$ uniform defined by the authors in a previous work, and which are generalizations of known classical results of ordinary calculus.